Employee Career: Effect of Administrative Competence, Social Capital and Performance (International Journal of Scientific Research and Management (IJSRM), 2018)
As organization grows and develops in dynamic globalization, employee is a valuable asset for organization and the need for qualified human resources is increases. The purpose of this research is aims to examine the influence of Administrative Competence, Social Capital and Performance to Employee Career of Mercu Buana University, using path analysis method in quantitative approach. Sample of this research was 185 employees of Mercu Buana University. Result of this research indicates that there is direct effect of competence to employee career which values 0,259, there is direct effect of performance to employee career which values 0,218, there is direct effect of social capital to employee career which values 0,213, there is direct effect of competence to performance which values 0,342, there is direct effect of social capital to performance which values 0,300. Thus it can be explained that the most direct influence to Employee Career and Performance is Competence.